Immuno-biologicals —the saviour of cattle against Rinderpest and Haemorrhagic Septicaemia - Mishra, Bina; Kumar, Bablu; Chaturvedi, V. K. (Indian Farming, 2015)
The Biological Products Division at the IVRI is proudly and untiringly serving by providing good quality vaccines and diagnostics at affordable price to veterinary professionals, stakeholders and above all protecting and enriching our diversified heritage of poultry and livestock population.